Determinants of Ecological Decisions of Users of Single-Family Houses in Poland in the Field of Energy Generation - Łukasz Kuźmiński; Joanna Dynowska; Rafał Nagaj; Sergiy Kozmenko; Tomasz Norek; Marcin Rabe; Andrzej Gawlik; Katarzyna Widera (Energies)
Since the early years of the 21st century, there has been a clear critique of the diotic way of farming in the international scientific arena, emphasizing that the existing models of economic development are exacerbating social inequalities and overexploiting natural resources. At the same time, the literature promotes the implementation of a new way of farming that takes into account environmental, social, and economic concerns. We have brought together new methods and ways of farming in these areas into one broad concept, called the conclusion of sustainable development. Within this concept, particular emphasis has been placed on sustainable energy development, the intensive development of technologies based on renewable energy sources, and the advancement of end-user awareness of modern technologies. The aim of this paper was to identify the factors that determine the ecological attitude of users of single-family houses in Poland when making strategic energy decisions related to the choice of heating devices in a household. To solve this research problem, the authors conducted a nationwide survey on a representative sample of single-family house users. In turn, the results were analyzed using log-linear analysis. The results showed that the determinants of the ecological nature of such energy decisions are primarily the age of the house users and their level of education. It was found that younger people are significantly more likely to think about ecology when making decisions related to how a building is heated than older people. In addition, people with a higher level of education are more likely to think about ecology when making such decisions than those with a lower level of education. Findings showed that the gender of the occupant of a single-family house, as well as the size of the town in which the building is located, have no significant impact on the ecological nature of decisions related to the choice of the method of obtaining energy for home heating. It was also shown that territorial variation, i.e., the region of the country, had no effect on this issue. The identification of socio-demographic determinants of the ecological nature of decisions related to the choice of heating devices in single-family houses in Poland fills the research gap and thus contributes to the literature in this area.